Convergent neural correlates of prenatal exposure to air pollution and behavioral phenotypes of risk for internalizing and externalizing problems: Potential biological and cognitive pathways. (June 2022) - Margolis, Amy E.; Liu, Ran; Conceição, Vasco A.; Ramphal, Bruce; Pagliaccio, David; DeSerisy, Mariah L.; Koe, Emily; Selmanovic, Ena; Raudales, Amarelis; Emanet, Nur; Quinn, Aurabelle E.; Beebe, Beatrice; et al.
Abstract: Humans are ubiquitously exposed to neurotoxicants in air pollution, causing increased risk for psychiatric outcomes. Effects of prenatal exposure to air pollution on early emerging behavioral phenotypes that increase risk of psychopathology remain understudied. We review animal models that represent analogues of human behavioral phenotypes that are risk markers for internalizing and externalizing problems (behavioral inhibition, behavioral exuberance, irritability), and identify commonalities among the neural mechanisms underlying these behavioral phenotypes and the neural targets of three types of air pollutants (polycyclic aromatic hydrocarbons, traffic-related air pollutants, fine particulate matter < 2.5 µm). We conclude that prenatal exposure to air pollutants increases risk for behavioral inhibition and irritability through distinct mechanisms, including altered dopaminergic signaling and hippocampal morphology, neuroinflammation, and decreased brain-derived neurotrophic factor expression. Future studies should investigate these effects in human longitudinal studies incorporating complex exposure measurement methods, neuroimaging, and behavioral characterization of temperament phenotypes and neurocognitive processing to facilitate efforts aimed at improving long-lasting developmental benefits for children, particularly those living in areas with high levels of exposure. Highlights: Air pollution alters dopamine, BDNF, and hippocampal structure in animal models. Neural mechanisms of risk markers of psychopathology are vulnerable to exposure. Exposure may increase risk for social anxiety and irritability via these mechanisms.